Taxonomic and ecological studies of actinomycetes from Vietnam: isolation and genus - level diversity - Duong Van Hop (Nature publishing group, 2016)
Actinomycetes were isolated from 109 soil and 93 leaf-litter samples collected at five sites in Vietnam between 2005 and 2008 using the rehydration-centrifugation (RC) method, sodium dodecyl sulfate-yeast extract dilution method, dry-heating method and oil-separation method in conjunction with humic acid-vitamin agar as an isolation medium. A total of 1882 strains were identified as Vietnamese (VN)-actinomycetes including 1080 (57%) streptomycetes (the genus Streptomyces isolates) and 802 (43%) non-streptomycetes. The 16S ribosomal RNA gene sequences of the VN-actinomycetes were analyzed using BLAST searches. The results showed that these isolates belonged to 53 genera distributed among 21 families. Approximately 90% of these strains were members of three families: Streptomycetaceae (1087 strains, 58%); Micromonosporaceae (516 strains, 27%); and Streptosporangiaceae (89 strains, 5%). Motile actinomycetes of the genera Actinoplanes, Kineosporia and Cryptosporangium, which have quite common morphological characteristics, were frequently isolated from leaf-litter samples using the RC method. It is possible that these three genera acquired common properties during a process of convergent evolution. By contrast, strains belonging to the suborder Streptosporangineae were exclusively isolated from soils. A comparison of the sampling sites revealed no significant difference in taxonomic diversity between these sites. Among the non-streptomycetes, 156 strains (19%) were considered as new taxa distributed into 21 genera belonging to 12 families. Interestingly, the isolation of actinomycetes from leaf-litter samples using the RC method proved to be the most efficient way to isolate new actinomycetes in Vietnam, especially the Micromonosporaceae species.